Quantifying bargaining power in supply chains: Essential for merger control - Yann Delaprez; Morgane Guignard (DIW Weekly Report, 2024)
Merger control plays a central role in competition policy. When assessing proposed mergers, Competition Authorities should consider its impact on all relevant markets. Large mergers between manufacturers typically impact competition, thus requiring the approval of Competition Authorities. Divestitures are often a condition of merger approval. This report investigates the effectiveness of implementing such merger remedies when bargaining between manufacturers and retailers is a key market feature. We examine the upstream merger between DEMB and Mondeléz that was approved by the European Commission in May 2015, subject to a divestiture. The divestiture indeed helped to mitigate the negative impacts of the merger. From the consumer's point of view, divestitures should take place in favor of manufacturers with less bargaining power.
Keywords: D12; L11; L51; L40; 330; Bargaining Power; Merger; Competition Authority; Consumer Surplus